2019
DOI: 10.1016/j.intman.2019.03.002
|View full text |Cite
|
Sign up to set email alerts
|

False foe? When and how code switching practices can support knowledge sharing in multinational corporations

Abstract: The operating environment of multinational corporations (MNC) is multilingual, adding significant complexity to knowledge-sharing interactions between employees. In this paper, we explore how knowledge sharing in MNCs is influenced by code switching, or shifting between languages during interaction. Previous international business research has mostly described codeswitching as a behavior that has a negative impact on knowledge sharing by creating distrust and exclusion. Our case study of a major Finnish MNC fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 97 publications
0
16
0
Order By: Relevance
“…Scientists doing policy-relevant extension work require different rules of engagement when their political beliefs and advocacy goals do not align with stakeholders. Moreover, the inadvertent code-switching we observed in experienced extension scientists could be classified as a strategic behavior to promote knowledge exchange, common language production between cultural groups, and encourage specific outcomes [77]. Becoming aware of and intentional about code-switching between academic and agricultural worlds could help scientists in agribusiness spaces.…”
Section: Training For Scientists Engaging With Agricultural Groupsmentioning
confidence: 94%
“…Scientists doing policy-relevant extension work require different rules of engagement when their political beliefs and advocacy goals do not align with stakeholders. Moreover, the inadvertent code-switching we observed in experienced extension scientists could be classified as a strategic behavior to promote knowledge exchange, common language production between cultural groups, and encourage specific outcomes [77]. Becoming aware of and intentional about code-switching between academic and agricultural worlds could help scientists in agribusiness spaces.…”
Section: Training For Scientists Engaging With Agricultural Groupsmentioning
confidence: 94%
“…It can be disconcerting for participants in a meeting to switch from the de facto language of the meeting (often English) into a language which is spoken only by a few other participants. This is termed ‘code switching’ (Ahmada and Barner-Rasmussen, 2019; Sesa Dogru et al, 2021). This often occurs when there is an element of stress in the discussions, perhaps from a linguistic misunderstanding and participants with a common second language decide that reaching a consensus will be facilitated by a discussion in this language.…”
Section: Code Switching and Workaroundsmentioning
confidence: 99%
“…However, the Organization for Economic Cooperation and Development Working Group found large cross-national variations in the availability and use of telecommunications technologies to support health-care delivery (Zelmer et al, 2017). Furthermore, the work of Ahmad and Barner-Rasmussen (2019) found that the management of information technologies could facilitate knowledge creation. Hence, we argue that ICT usage enables project teams to promote performance.…”
Section: Hypothesismentioning
confidence: 99%
“…Tacit knowledge is the core value element for enterprises to obtain competitive advantages in the knowledge economy era (Jin-Feng et al, 2017). The operating environment of multinational corporations (MNC) is multilingual, adding complexity to KS among employees (Ahmad and Barner-Rasmussen, 2019), which makes tacit KS among team members more difficult. Many scholars have discovered that KS based on individual abilities plays a key role in promoting team innovation performance (Du Chatenier et al, 2010).…”
Section: Hypothesismentioning
confidence: 99%
See 1 more Smart Citation